Blurred Waters of the Biographical Element. Editorial Introduction - Agnieszka Dauksza (Zagadnienia Rodzajów Literackich, 2021)
Inspired by Clifford Geertz’s concept, the author analyses blurred genres on the example of biographies, focusing on their contemporary transformations, while scrutinizing their formal, methodological and audience-related (possible reasons behind their popularity) aspects. The ethical dimension of the biographer’s work is crucial, and here it is examined from the perspective of the writer’s personal involvement and the emotional community of readers (as defined by Barbara Rosenwein). The study also analyses biographies when they are perceived as a type of testimony, experience, an act of creating potential histories, or as critical works. From this perspective, writing a biography is like inciting comprehension by re-evaluating the meaning of somebody’s experiences and engaging them with the modern readers’ experience. In all probability, the key is not the authenticity of the presented reality, but enabling the reader to immerse themselves in the flow of the story so that reading the book becomes a significant experience in itself. What the reader seems to require is for the devices that are typical for novel-like narration to be combined with nonfictional forms. Thus, genre blurring is, in fact, a basis for renegotiating the pact between authors and readers, where both sides are well aware of how ambiguous it is to write about an absent third party, realizing that it is necessary to omit facts, be concise, make sense of convoluted events, and to extract the essence in things that seemingly look chaotic.